Effects of sorbitol and sucrose on soybean-urease induced calcium carbonate precipitate - Mingdong Li; Yuanjiang Yang; Shiai Zhang; Xuedong Chen; Hanshuo Yin; Liping Zhu (Biogeotechnics)
This study explores the effects of two nucleating agents, sucrose and sorbitol, on soybean-urease induced calcium carbonate precipitation (SICP) at a crystal level. Comparative studies on the mineral composition, crystal size, surface morphologies and thermal stability of SICP samples with/without nucleating agent were investigated with high resolution XRD, SEM and synchronous thermal analyzer (STA), respectively. The results show the introductions of sorbitol or sucrose to SICP reduce the content of vaterite(114) from 10.07% to 1.81%–3.93%, indicating their effect on transforming vaterite into stabler calcite. Sorbitol can enlarge the crystals and improve the thermostability of SICP, indicating an improvement of the crystallinity of SICP. The sucrose-regulated SICP shows medium thermostability which is worse than SICP without the nucleating agent, indicating the addition of sucrose reduces the crystallinity of SICP. Sorbitol is an effective nucleating agent that can improve the behaviors all-around, while sucrose increases the calcite content of SICP but inhibits the crystallinity of SICP. This study reveals the regulations of SICP because of the introduction of sorbitol or sucrose, and provides guidance to the subsequent engineering application of SICP.